The relationship between visual ability assessment and competitive boxing performance in female amateur boxers - Xiao, Youlin; Zhong, Huihui; Gao, Dongxu; Zhuang, Mingnan; Long, Yuankun; Wei, Qiang; Wang, Dexin; Zhang, Peng; Zhao, Zihao; Chen, Chao (Frontiers in Physiology, 2025)
IntroductionThe relationship between visual abilities and punching performance has received considerable attention in sports science, but research on female amateur boxers remains limited. This study investigates the correlation between visual‑motor abilities and punching performance in female amateur boxers.MethodsA total of 26 trained female boxers participated in the study, and their visual abilities were assessed using the Senaptec Sensory Station. The visual ability tests included measures of visual clarity (VC), contrast sensitivity (CS), depth perception (DP), perceptual span (PS), multiple object tracking (MOT), reaction time (RT), eye‑hand coordination (EHC), and Go/No‑Go (GNG). Punching performance was analyzed by evaluating the hit percentage (%Hit) in the National Boxing Championship.ResultsPearson correlation analysis showed that punching accuracy (%Hit) was strongly correlated with EHC, RT, PS, and DP. Stepwise regression analysis confirmed that these visual abilities significantly predicted punching performance, with EHC, RT, PS, and DP explaining 93.1% of the variance in %Hit.DiscussionThe results highlight the significant role of visual motor abilities in enhancing the punching performance of female boxers. The study suggests that training programs targeting these visual abilities, especially EHC, RT, and DP, could improve boxing performance. This research provides valuable insights into the role of vision in female boxing and suggests future directions for visual training in combat sports.